1976
DOI: 10.1159/000231595
|View full text |Cite
|
Sign up to set email alerts
|

Increased Vascular Permeability during Passive Peritoneal Anaphylaxis in the Rat

Abstract: Following intraperitoneal sensitisation of rats with rat serum containing reaginic antibody, intravenous injection of blue dye and intraperitoneal challenge with antigen caused a release of histamine, slow-reacting substance of anaphylaxis (SRS-A) and dye into their peritoneal fluids. The times taken to reach peak concentrations after challenge were less than 2 min for histamine and between 5 and 10 min for SRS-A, whilst concentrations of dye were still increasing after 2½ h. The amounts of histamine released … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 6 publications
2
24
0
Order By: Relevance
“…Our results correspond to those of previous investi gators who studied rat passive peritoneal anaphylaxis (PPA) under similar conditions [9]. We found that H was released shortly after challenge, and already de clined within 6-20 min.…”
Section: Results and Conclusionsupporting
confidence: 91%
“…Our results correspond to those of previous investi gators who studied rat passive peritoneal anaphylaxis (PPA) under similar conditions [9]. We found that H was released shortly after challenge, and already de clined within 6-20 min.…”
Section: Results and Conclusionsupporting
confidence: 91%
“…The maximum BHR is attained within 5 min whereas LHR is much slower. Such an explosive release of mediators has been described in cytotoxic degranulation of human basophils [3] as well as in various experimental models in cluding passively sensitized rat peritoneal mast cells [11] and guinea pig lung [1]. The kinetics of release in blood is consistent with the sudden onset of some systemic ana phylactic reactions which may be encoun tered in clinical practice.…”
Section: Discussionmentioning
confidence: 66%
“…1 B could arise from antagonism of the test drugs to anaphylactic mediators. Out of the possible mediators, histamine has been reported to contribute to 60% of the amount of dye leaked in rat PPA (4). Therefore, we investigated the effect of TA-5707 on histamine-induced dye leakage.…”
Section: Resultsmentioning
confidence: 99%